Oil Facilities Surveillance Using an Autonomous Quadrotor - Abdul- Samed, Baqir Nasser (Journal of Petroleum Research and Studies, 2022)
This work addresses using the autonomous quadrotor or unmanned aerial vehicle (UAV) for surveillance of oil fields, Facilities and pipelines since that can be very costly and dangerous specially in dangerous zones. This topic is very important because of the money consuming to repair and protect these oil facilities. Quadrotors are very small Vertical take-off landing (VTOL) helicopter, cheap, easy to use and has many other fields of applications. Quadrotor’s dynamic model involves nonlinearity, uncertainties, and coupling which makes the Quadrotor has a very complex system. PID controllers are proposed for controlling the quadrotor altitude through different environments during different missions. To drive the quadrotor to follow the desired trajectory pure pursuit algorithm (PPA) will be use. The simulation results will be pretested using the visual simulator named Gazebo with the aid of ROS to connected with the MATLAB to show the movement of the quadrotor insides different environments.